Lost in Translation: Navigating Linguistic Challenges in Lesotho High Court Trials - Makhetsi Makha-Ntlaloe; Teboho Reginah Mphi; Mape John Mohlomi (REiLA, 2023)
Court interpreting services are an essential component of the Lesotho’s legal system to ensure that everyone has access to justice and can present their cases in the language of their choice, more especially at the Lesotho High Court where English is the language of the court. Effective court interpreting requires interpreters with, among other things, high level of linguistic and cultural proficiency in their working languages, strategic competence, and a set of specific skills. However, the lack of formal professional training for court interpreters can have serious consequences on both the communication and the decisions of the court.  Following the methodological principles of a qualitative case study explored strategies employed by the Lesotho High Court interpreters in their attempt to address linguistic challenges that they often encounter during their facilitation of communication between judges, lawyers and plaintiff/defendant/witnesses. The study further examined how such strategies may  affect communication of the intended message in the interpreter’s renditions. Employing a pragmatic approach guided by Gricean maxims, this paper discussed a purposive sample of 19 excerpts extracted from the transcripts made from ten audio recordings of criminal cases from the Lesotho High Court. The study discovered that such strategies were employing to address linguistic challenges such as terminological challenges, long sentences and incomplete or too brief source language utterances. The study further established that the use of the identified strategies may distort the original speaker’s intended message and hence misinform the witnesses and/or target recipients, which in turn could result in an unfair trial. To enhance the court interpreting process to uphold fairness and clarity in legal proceedings, this paper therefore recommends that the Lesotho High Court should provide formal training to its interpreters to raise their awareness of the strengths and weaknesses of the strategies they use.